Fully graph solution of the sensitivity of switched circuits - Brtník, Bohumil (My University, 2018)
The most general parameter of the electronic circuit is its sensitivity. Sensitivity analysis helps circuit designers to determine boundaries to predict the variations that a particular design variable will generate in a target specifications, if it differs from what is previously assumed. There are two basic methods for calculating the sensitivity: matrix methods and graph methods. The method described in this article is based on a graph, that contains separate input ad output nodes for each phase. This makes it possible to determine the transmission sensitivity even between partial switching phases. The described fully-graph method is suitable for switched current circuits and switched capacitors circuits, too.
Plně grafové řešení citlivosti spínaných obvodů
Keywords: Sensitivity; switched capacitors; switched currents; graph method; citlivost; spínaná kondenzátory; spínané proudy; grafová metoda